Interface Directed Self Assembly of Cell-Laden Microgels - Zamanian, Behnam (2010)
Cell-laden hydrogels show great promise for creating engineered tissues. However, a major shortcoming with these systems has been the inability to fabricate structures with controlled microscale features on a biologically relevant length scale. Here we demonstrate a rapid method for creating centimeter-scale, cell-laden hydrogels through the assembly of shape-controlled microgels. This was achieved by using an approach that uses the liquid-air interface of a hydrophobic solution to drive the assembly of microgels. Cell-laden microgels of specific shapes were randomly placed on the surface of a high density, hydrophobic solution and induced to aggregate and were subsequently crosslinked into macroscale tissue-like structures. The resultant assemblies were cell-laden hydrogel sheets consisting of tightly-packed ordered microgel units. In addition, a hierarchical approach created complex multi-gel building blocks which were then assembled into tissues with precise spatial control over the cell distribution. These data demonstrate that forces at an air-liquid interface can be used to self-assemble spatially controllable, co-cultured tissue-like structures.